Student’s Self Efficacy Differences Review From The Use of Android-Based Media and Powerpoint to Overcome Anxiety in Online Learning - Ikhsanty, Yuliana Rizka; Basori, Basori; Aristyagama, Yusfia Hafid (IJIE (Indonesian Journal of Informatics Education), 2021)
Online learning that is not accompanied by innovation in teaching causes anxiety in students. This anxiety can be overcome by increasing self efficacy. Developing learning media can be an effort to increase student self efficacy. So, this Study was intended to find out: (1) whether there was a significant difference between the use of android-based learning and powerpoint on students’s self efficacy in Computer and This study used post-test only control design method and t-test to compare 1st experimental group (teaching with powerpoint) and 2nd experimental group (teaching with android media).  A total of 71 students of 1st grade RPL at one of vocational school in Karanganyar were randomly selected as samples. The results of self-efficacy were measured by a questionnaire that was validated by 4 expert judgments. Based on statistical results, shows a significant difference between 1st experimental group (teaching with powerpoint) and 2nd experimental group (teaching with android media) on their self-efficacy questionnaire. The 1st experimental group got a lower score than the 2nd experimental group with a gap score of 9.71. The t-test value for df = 69 is 3,439 which is higher than ttable = 1,994. The effectiveness of android media is relatively high based on d Cohen's calculations with a score of 0.945. The results of this study indicate that there is a significant difference between the use of android-based learning and powerpoint on students self-efficacy in basic computer network subjects, moreover android-based learning might be an effective medium to increase students self-efficacy in overcoming online learning anxiety.